2016
DOI: 10.1371/journal.pone.0165892
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Assessment of Novel Helical/Spiral Grafts with Improved Hemodynamics for Distal Graft Anastomoses

Abstract: In the present work, numerical simulations were conducted for a typical end-to-side distal graft anastomosis to assess the effects of inducing secondary flow, which is believed to remove unfavourable flow environment. Simulations were carried out for four models, generated based on two main features of 'out-of-plane helicity' and 'spiral ridge' in the grafts as well as their combination. Following a qualitative comparison against in vitro data, various mean flow and hemodynamic parameters were compared and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 54 publications
0
37
2
Order By: Relevance
“…These resistance and capacitance values are based on measured blood pressure and flow rates, however, acquiring these model parameters can be a difficult task, often due to practical difficulties in the acquisition of pressure and flow data of all required sites, or the measurement data available is insufficient for accurately estimating these model parameters 14 . Hence, despite more reliable methods existing, it is still common amongst the cardiovascular research community to use simpler outlet BCs such as zero pressure [15][16][17][18][19][20][21][22] , flow ratios based on Murray's Law (ML) 20 and the combination of flow ratios based on ML and in vivo data 23,24 . To put this into some perspective, during the 2013 intracranial aneurysm rupture challenge, 46% of 26 participating CFD groups defined zero pressure at all outlets, 46% applied flow splits (either arbitrary values or based on ML), whilst 8% implemented a 3-Element Windkessel model 20 .…”
Section: Introductionmentioning
confidence: 99%
“…These resistance and capacitance values are based on measured blood pressure and flow rates, however, acquiring these model parameters can be a difficult task, often due to practical difficulties in the acquisition of pressure and flow data of all required sites, or the measurement data available is insufficient for accurately estimating these model parameters 14 . Hence, despite more reliable methods existing, it is still common amongst the cardiovascular research community to use simpler outlet BCs such as zero pressure [15][16][17][18][19][20][21][22] , flow ratios based on Murray's Law (ML) 20 and the combination of flow ratios based on ML and in vivo data 23,24 . To put this into some perspective, during the 2013 intracranial aneurysm rupture challenge, 46% of 26 participating CFD groups defined zero pressure at all outlets, 46% applied flow splits (either arbitrary values or based on ML), whilst 8% implemented a 3-Element Windkessel model 20 .…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously demonstrated that different flow patterns (and in our case pathologically-relevant elevated flow) changes endothelial behaviour and in particular the response to noxious stimuli that induce endothelial dysfunction [17,37,38]. In addition, the CFD simulations and subsequent statistical post-processing indicted that several OCT-defined erosions occurred in regions with modest or no stenosis, where the predominant flow feature was oscillatory shear stress (defined through OSI) [48,49]. Low time averaged wall shear stress or elevated OSI values strongly correlate with the focal predilection sites for atherosclerosis [32,[50][51][52] and tend to activate endothelial cells, priming them for inflammatory activation and apoptosis [28,34,53].…”
Section: Discussionmentioning
confidence: 55%
“…The localization of various lesions including atherosclerosis and thrombosis has been extensively studied and have shown to be related to different local haemodynamic metrics including some of the work of the present authors (Deyranlou et al 2020;Kabinejadian et al 2016;Keshmiri et al 2016;McElroy et al 2016a;McElroy and Keshmiri 2018;Ruiz-Soler et al 2017;Swanson et al 2020). These haemodynamic parameters can be directly derived from the flow velocity fields obtained by CFD-based simulation tools.…”
Section: Haemodynamic Parametersmentioning
confidence: 99%
“…Despite more reliable methods existing, it is still common amongst the cardiovascular research community to use simpler outlet BCs such as zero-pressure (Cheng et al 2014;Deyranlou et al 2020;Janiga et al 2015;Kabinejadian et al 2016;Karmonik et al 2014Karmonik et al , 2012bMcElroy et al 2016b;Moon et al 2014;Ruiz-Soler et al 2017;Shang et al 2015). Running 'Tests 0-6' using a conventional zero-pressure BC for all outlets produces significantly different results and misleading conclusions when compared against using a threeelement Windkessel model.…”
Section: Effects Of Using Conventional Zero-pressure Boundary Conditionmentioning
confidence: 99%